Photorheologic Silicone Composites with Adaptive Properties by Utilizing Light‐Degradable Organosilica Nanoparticles as Fillers - Florian Klodwig; Laura Finck; Nina Ehlert; Peter Behrens; Henning Menzel; Sebastian Polarz (Advanced Materials Interfaces)
Abstract Implementing inorganic filler particles is a powerful method for improving the mechanical properties of polymer composites. The physical properties are determined by the interaction of the filler with the polymer. Thus, factors like the surface‐to‐volume ratio and surface modification are important. Besides the strategies of influencing these physical properties by a prior modification of the filler, this approach applies a post‐treatment of the composite. The present publication focuses on bringing stimuli‐responsive properties to a composite material by changing the chemical composition and structure of the filler particles. Instead of creating a responsive polymer, the concept is to use photo‐degradable organosilica nanoparticles that can change the mechanical properties of a polymer/filler composite after it has been prepared. After the synthesis of nitrobenzyl ether containing organosilica nanoparticles and the investigation of the photochemical processes, the preparation of the composites with silicones is described. Vinyl groups are attached to the surfaces to secure a homogeneous distribution of the filler particles inside the polymer matrix. After light‐induced decomposition, the mechanical properties are investigated. Other than expected, the material becomes stiffer, which is explained by an increase in the surface area of the silica particles, accompanied by the emergence of hydroxy groups that interact with the polysiloxane.